Pre-vaccination screening strategies for the use of the CYD-TDV dengue vaccine: A meeting report. Issue 36 (23rd August 2019) - Wilder-Smith, A.; Smith, P.G.; Luo, R.; Kelly-Cirino, C.; Curry, D.; Larson, H.; Durbin, A.; Chu, M.; Tharmaphornpilas, P.; Ng, L.C.; Sartori, A.M.C.; Luna, E.J.A.; et al.
Abstract: The first licensed dengue vaccine, CYD-TDV (Dengvaxia) is efficacious in seropositive individuals, but increases the risk for severe dengue in seronegative persons about two years after administration of the first dose. For countries considering the introduction of Dengvaxia, WHO recommends a pre-vaccination screening strategy whereby only persons with evidence of a past dengue infection would be vaccinated. Policy-makers need to consider the risk-benefit of vaccination strategies based on such screening tests, the optimal age to introduce the vaccine, communication and implementation strategies. To address these questions, the Global Dengue and Aedes-transmitted diseases Consortium (GDAC) organized a 3-day workshop in January 2019 with country representatives from Asia and Latin America. The meeting discussions highlighted many challenges in introducing Dengvaxia, in terms of screening test characteristics, costs of such tests combined with a 3-dose schedule, logistics, achieving high coverage rates, vaccine confidence and communication; more challenges than for any other vaccine introduction programme. A screening test would require a high specificity to minimize individual risk, and at the same time high sensitivity to maximize individual and population benefit. The underlying seroprevalence dependent positive predictive value is the best indicator for an acceptable safety profile of a pre-vaccination screening strategy. The working groups discussed many possible implementation strategies. Addressing the bottlenecks in school-based vaccine introduction for Dengvaxia will also benefit other vaccines such as HPV and booster doses for tetanus and pertussis. Levels of public trust are highly variable and context specific, and understanding of population perceptions and concerns is essential to tailor interventions, monitor and mitigate risks.